FOOD AND NUTRITION INSECURITY AND RISK FACTORS FOR CHRONIC NONCOMMUNICABLE DISEASES AMONG SOLID WASTE COLLECTORS - Maria Rafaela Martins de Oliveira; Roseane Saraiva de Santiago Lima; Francisco Regis da Silva; Luisa Maria Oliveira Pinto; Rafaella Maria Monteiro Sampaio (Universidade do Estado do Rio de Janeiro, 2018)
Previous studies have shown a relationship between food and nutrition insecurity and chronic noncommunicable diseases (NCDs), and it should be noted that nutritional deficiencies and hunger are not the only forms of expression of this condition. The aim of this study was to evaluate the occurrence of food and nutrition insecurity and the risk factors for the development of NCDs among solid waste collectors in a municipality in the countryside of Ceará State (CE), Brazil. A cross-sectional study was conducted with 32 workers, aged 20-66 years. A structured questionnaire was applied to collect personal, socioeconomic, dietary and anthropometric data. Food and nutrition insecurity was evaluated through the Brazilian Food Insecurity Scale (EBIA). There was food and nutrition insecurity in 100% of the sample, low level of education (78.12%) and low income (87.5%), prevalence of overweight (25.0%) and obesity (31.26%) and poor consumption of fruits, vegetables and vegetables. The was a high proportion of moderate and severe food insecurity, and workers presented risk factors for the onset of NCDs. DOI: 10.12957/demetra.2018.34088